Efecto de la velocidad de avance y corriente de trabajo en la calidad de las soldaduras producidas por flux cored con electrodo tubular - Piracoca Balaguera, Julieth Andrea; Diaz Torres, Jeison Felipe (Universidad Antonio Nariño, 2021)
In this project, an analysis of the effect of the application parameters (forward speed and current), on the quality, mechanical properties and composition of the gas-protected tubular electrode weld, applied by the flux cored process, on pieces of A572 steel. The development of the project will be presented in 4 methodological phases that cover the theoretical analysis and the state of the art of the flux cored process, passing through the stage of test tube preparation, characterization of the same, until culminating in the writing of reports that condense the results obtained. The quality of the weld will be evaluated using non-destructive techniques such as visual inspection, penetrating liquids, magnetic particles and ultrasound, while mechanical tests such as stress and microhardness tests will be carried out in order to determine the integrity of the applied weld at different current conditions and forward speed. As a result of the tests carried out on the quality of the weld, taking into account the working conditions such as current, it can be indicated that when using the highest value, the properties of the steel were found to be more favorable, revealing that the material it behaves in a more fragile way and achieves a greater measure of hardness, taking into account that in the elastic zone of the material, no significant deformations are generated when applying great forces. For the different conditions of advance speed, it can be highlighted that by applying the weld faster, better conditions were obtained during the tests, showing, for example, an average increase of 50% in resistance to elastic deformation.